Characterization and Evaluation of Antioxidant Activity of Aloe schelpei Reynolds - Teka T; Kassahun H (Dove Medical Press, 2020)
Tekleab Teka, 1, 2 Haile Kassahun 1 1Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Tianjin State Key Laboratory of Modern Chinese Medicine, Tianjin Key Laboratory of TCM Chemistry and Analysis, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of ChinaCorrespondence: Tekleab Teka Email ttekleab@gmial.comBackground: The role of free radical reactions in disease pathology is well known to be involved in many acute and chronic disorders in human beings, such as diabetes, atherosclerosis, aging, immunosuppression and neurodegeneration. The search for new drugs of plant origin becomes increasingly urgent due to drug resistance. Aloe schelpei is an endemic Aloe species traditionally used for the treatment of infectious and chronic diseases.Aim: This study was conducted to evaluate free radical scavenging activities of leaf latex of Aloe schelpei and its isolated compounds.Methods: The leaf latex of A. schelpei was subjected to preparative thin-layer chromatography to afford three compounds. Free radical scavenging activities of the leaf latex and its constituents was carried out using a 2, 2-diphenyl-1-picrylhydrazyl method.Results: Phytochemical investigation of the leaf latex Aloe schelpei by prepartive thin layer chromatography led to the isolation of three compounds, identified as microdontin A/B ( 1), aloin A/B ( 2) and aloinoside A/B ( 3). The results showed that the leaf latex had a strong free radical scavenging activity reaching a maximum of 84.3% at a concentration of 100 μg/mL, and with an IC 50 value of 25.3 ± 2.45 μg/mL (p < 0.05). Among the isolated compounds, microdontin A/B ( 1) was found to have the strongest free radical scavenging activity with an IC 50 value of 0.07 ± 0.005 mμ, followed by aloinoside A/B (IC 50 = 0.13 ± 0.01 mM) and aloin A/B (IC 50 = 0.15 ± 0.02 mM).Conclusion: The traditional medicinal practice of the leaf latex may be due to the antioxidant activities of the leaf latex of A. schelpei and the isolated compounds.Keywords: Aloe schelpei, 2, 2-diphenyl-1-picrylhydrazyl, DPPH, microdontin A/B, aloin A/B, aloinoside A/B, antioxidant